2021
DOI: 10.1002/pld3.342
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy‐based diagnostics of water deficit and salinity stresses in two accessions of peanut

Abstract: Water deficit and salinity are two major abiotic stresses that have tremendous effect on crop yield worldwide. Timely identification of these stresses can help limit associated yield loss. Confirmatory detection and identification of water deficit stress can also enable proper irrigation management. Traditionally, unmanned aerial vehicle (UAV)‐based imaging and satellite‐based imaging, together with visual field observation, are used for diagnostics of such stresses. However, these approaches can only detect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…For instance, in the Raman spectra collected from wheat exposed to drought, we observed a small decrease in the intensity of carotenoid (1000,1048,1120,1155,1184,1218, and 1525 cm -1 ) bands, Figure 1 and Table S1. These observations suggest that drought causes a decrease in the concentration of carotenoids in plants, thereby showing harmony with earlier findings by Morey and co-workers (Morey et al, 2021). We observed even greater decrease in the intensity of carotenoid vibrations in the spectra collected from ND plants.…”
Section: Resultssupporting
confidence: 93%
“…For instance, in the Raman spectra collected from wheat exposed to drought, we observed a small decrease in the intensity of carotenoid (1000,1048,1120,1155,1184,1218, and 1525 cm -1 ) bands, Figure 1 and Table S1. These observations suggest that drought causes a decrease in the concentration of carotenoids in plants, thereby showing harmony with earlier findings by Morey and co-workers (Morey et al, 2021). We observed even greater decrease in the intensity of carotenoid vibrations in the spectra collected from ND plants.…”
Section: Resultssupporting
confidence: 93%
“…A summary of the substances mentioned in these studies is shown in Table 2. [142,144,147,148,152,[176][177][178] As follows from Table 2, these compounds belong to both primary and special metabolites. Some of them may be involved in both roles, depending on the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Partial least squares-discriminant analysis (PLS-DA) is one of the most widely used classification algorithms to deal with the multicollinearity problem of high-dimensional spectral data [ 16 ]. This method has been used in the context of genotype classification, disease detection, and the physiological states of crops [ 16 , 17 , 18 ]. On the other hand, Artificial Neural Networks (ANNs) have emerged as a powerful tool for the predictive modeling of big data.…”
Section: Introductionmentioning
confidence: 99%